INTEGRATED LEARNING at SMA TERPADU DARUSSALAM RAJAPOLAH TASIKMALAYA - Muhammad Hasan Basari; Engkus Kuswarno; Hanafiah; Achmad Mudrikah (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2022)
The purpose of this study was to obtain an overview, knowledge and describe about integrated learning in a pesantren-based school at SMA Terpadu Darussalam Rajapolah Tasikmalaya. The main result of this research is that integrated learning in a pesantren-based school at SMA Terpadu Darussalam Rajapolah Tasikmalaya uses an integrated one-lesson learning model that stands alone and integrates with the integrated curriculum, twenty-four hour parenting and learning time in the lesson schedule. The conclusion is that integrated learning in pesantren-based schools at SMA Terpadu Darussalam Rajapolah Tasikmalaya uses an integrated one-lesson learning model that stands alone and integrates with integrated curriculum, twenty-four hour parenting and learning time in the lesson schedule. Integrated learning emphasizes the integration of general learning which refers to the 2013 curriculum by integrating the salafi pesantren curriculum and KMI Gontor. Supported by an integrated 24-hour upbringing of students in Islamic boarding schools and schools, integration of learning hours, educators and integration of learning materials to foster the noble character of students.